factorise fully a) \( x^{2}+7 x+12 \) \( = \) b) \( x^{2}-4 x-12 \) \( = \) c) \( x^{2}+4 x-12 \) \( = \) d) \( a^{2}-9 a+20 \)
Solución de tutoría real
Responder
Solución
Revisado y aprobado por el equipo de tutoría de UpStudy
Extra Insights
To factorise the given quadratic expressions: a) \( x^{2}+7 x+12 = (x+3)(x+4) \) b) \( x^{2}-4 x-12 = (x-6)(x+2) \) c) \( x^{2}+4 x-12 = (x+6)(x-2) \) d) \( a^{2}-9 a+20 = (a-4)(a-5) \) Got it? Let’s dive a bit deeper! The beauty of quadratics lies in their patterns! Recognizing factors of the constant term that add up to the middle coefficient can save time. For instance, in part (a), we identified that 3 and 4 multiply to 12 and add to 7 swiftly made the factorization clear. Don't overlook the special cases! Quadratics that take the form \( x^2 - a^2 \) can be factored using the difference of squares formula, while \( x^2 + 2ax + a^2 \) follows the perfect square trinomial pattern. Understanding these will make factorization second nature!